Soft Law and the Protection of Climate Migrants: A Case Study of Bangladesh - Alimuddin, Sitti Zarina; Muhammad, Ali (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2023)
The study seeks to explain the importance of the ‘soft law’ framework in protecting climate migrants and internally displaced persons in Bangladesh. We argue that the present protection gaps may be addressed without requiring new, enforceable regulations. This study employs qualitative research methodologies based on literature research. Additionally, we draw on secondary data from internet news and academic papers pertinent to the topics discussed in this work. From this research, we found that developing a soft law framework by the International non-governmental organizations (INGOs) and non-governmental organizations (NGOs) play an important role to assist Bangladeshi climate migrants. Soft law procedures allow increased inclusivity in global regulation and governance.